THE EFFECTIVENESS OF USING VOCABULARY SELF-COLLECTION STRATEGY (VSS) IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT AT THE EIGHTH GRADE STUDENTS OF SMP 25 PURWOREJO IN THE ACADEMIC YEAR OF 2019/2020 - Basuki Basuki (p-ISSN 2356-0576, 2020)
Abstract: This research is conducted to know the students’ reading comprehension and to find out whether or not use of vocabulary self-collection strategy (VSS) effective in teaching reading of SMP 25 Purworejo in the academic year of 2019/2020. The population of this research is 186 students of the eighth grade students of SMP 25 Purworejo in the academic year of 2019/2020 and the amount of sample is 30 students. From the computation, the result showed that the mean score of pre-test is 62.93 (sufficient category) and the mean of post-test is 77.07 (good category). It shows that the result of computation is t value obtained bigger than t table (3.705>2.000) it can be concluded that vocabulary self-collection strategy (vss)is effective to teaching reading Narrative text at the eighth grade students of SMP 25 Purworejo in the academic year of 2019/2020.Keywords: effectiveness, vocabulary self-collection strategy (vss), reading comprehension,narrative text.